(untitled) (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2012)
Research on Development of Integrated Website Science Book for International Standardized School aims to provide book that can be used by both teacher and students an International Standardized Schools as learning source. The book hopefully can give an overview to students and teachers in understanding science as an integrated subject, promoting of using English in science teaching and improving skill in using ICT. The research was carried out by Research and Development (R&D) which started from curriculum analysis for both KTSP and Cambridge. The book was constructed in a form of electronic book (e-book) which provides science knowledge in a form of themes that integrate the concepts of biology, physics and chemistry. English is used a formal language of this ebook. Result from trial use of the e-book in bilingual school revealed that this e-book fulfilled the criteria as it contain picture, animation, exercise and sound which interest student to read it. The usage of English in this e-book promote student to learning English. Most student were agree to say that the book is creative and it can be use in teaching learning process at junior high school, specifically in International standardized School . Penelitian Pengembangan Buku Terintegrasi Website Untuk Sains SMP SBI dan RSBI dilakukan dengan tujuan untuk menyediakan buku sains yang dapat dijadikan sebagai salah satu sumber belajar bagi guru dan siswa SMP di RSBI/SBI. Dengan dikembangkannya buku ini, diharapkan pembelajaran sains dapat mengembangkan pemahaman sains siswa secara terintegrasi, mengembangkan kemampuan berbahasa Inggris siswa, serta mengembangkan kemampuan dalam menggunakan teknologi informasi. Penelitian dilakukan melalui metode Reseach and Development (R&D) yang diawali dengan analisis kurikulum sains SMP berdasarkan KTSP dan kurikulum Cambridge. Penyajian buku berupa tema-tema yang mengintegrasikan konsep-konsep dalam fisika, kimia dan biologi dengan menggunakan Bahasa Inggris sebagai bahasa pengantar. Dari hasil uji kelayakan penggunaan buku yang dilakukan terhadap siswa SMP diperoleh bahwa e-book yang disusun memenuhi kriteria penggunaan e-book dalam aspek penyajian gambar, animasi, penggunaan huruf, penggunaan Bahasa Inggris sebagai bahasa pengantar, latihan serta kegiatan siswa. Secara umum, ebook yang dikembangkan dinilai memiliki kreativitas yang baik dan layak digunakan sebagai buku sumber dalam pembelajaran sains di SMP, khususnya di RSBI/SBI.